Motivations and Visit Intentions in A Local Tourist Destination: A Qualitative Analysis of Visitors to the Mpu Tantular Museum - Arintawati, Mei (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to determine the visitors’ motivations for visiting the Mpu Tantular Museum and their intentions for visiting. This research uses qualitative data techniques using the interview method with stages of data reduction, data presentation and decision-making. This research indicates that push or pull motivation can influence someone to visit the Mpu Tantular Museum. The museum is an educational tourist attraction that collects all ancient relics and regional cultural collections. The Mpu Tantular Museum can be used as a reference for learning that encourages a person’s motivation to visit the museum because of their own encouragement to learn about historical heritage or interesting motivation obtained from outside. Someone visits a museum to learn about past history, broaden their knowledge and look for something new. In the museum, they can observe objects from the past directly. The average museum visitor visits a museum because they want to know something new that they have never seen before. Museums also provide various access for visitors so that visitors have the opportunity to use facilities and services, research and study collections, and various information available. The attraction of the Mpu Tantular Museum, such as its collections, buildings, and learning facilities, is one of the factors that make people visit the museum.